Pengembangan Bahan Ajar IPA Interaktif Berbasis Flipbook pada Materi Siklus Air di Kelas V MI Miftahul Huda Lamong - Rizki Rahma Alami; A. Jauhar Fuad; Abbas Shofwan Matlail (Intellektika : Jurnal Ilmiah Mahasiswa, 2025)
This research and development is motivated by the fact that the learning of science subjects on the water cycle material is less in accordance with the characteristics of students. The limitations of teaching media in schools are educational problems that can hinder the success of the learning process. Researchers want to develop interactive science teaching materials on the water cycle material to increase the enthusiasm for learning of grade V SD/MI students. The purpose of this development research is to produce a product in the form of interactive science teaching materials in grade V on the water cycle material. This study uses the ADDIE development research model and design developed by Dick and Carry with 5 steps, namely analyzing, designing. Developing. Implementing. Evaluating. This research was conducted at MI Mifathul Huda Lamong with class V research subjects.The results of the research and development of interactive science teaching materials in grade V on the water cycle material at MI Miftahul Huda Lamong. In the development stage, the results were in the form of teaching materials developed consisting of 23 pages. This interactive science teaching material has received validity from experts (1) learning media experts of 93% with very good criteria (2) material experts of 85% with good criteria (3) student interest questionnaire of 95% with very good criteria.